Diseño de una metodología de auditoría de gestión para el sector Agroindustrial aplicada en la asociación "Núcleo Parroquial de la Pequeña Industria de Mindo" - cantón San Miguel de los Bancos - provincia Pichincha - Lata Hurtado, Elizabeth Cristina (2015)
The “Núcleo de la Pequeña Industria de Mindo” association, from its beginnings and to the present time, he meets producing cheese and yogurt to shower with his principal customer's request. Taking into consideration that the products that company offers are of massive consumption and with competitive characteristics on the market, to seen the imperious need to accomplish internal changes, establishing the Design of their processes, in order to be able to optimize times and to use in the best way his resources, so much economic like humans, as well as increasing the levels of production of the plant. The theoretic frame details itself in the first chapter that the investigation of present bases project, like also the necessary concepts for the development of the same one. In the second chapter “Núcleo de la Pequeña Industria de Mindo”, where he finds itself located, encounters the company's background the products that he offers, the raw material and resources. The third chapter presents the methodology to be applied to the company to measure levels of efficiency, effectiveness and economy of its processes. In the chapter the proposal of improvement shows four itself for which the manuals of processes and procedures are developed and it is presented economic investment that he must become for the better production. Finally there are the conclusions and recommendations that they rose when project accomplished present, which as they are a very important contribution for the company's executives “Núcleo de la Pequeña Industria de Mindo”.